Recent Developments in Reconfigurable and Multiband Antenna Technology. (13th March 2013) - Haider, N.; Caratelli, D.; Yarovoy, A. G.
Abstract : A comparative analysis of various reconfigurable and multiband antenna concepts is presented. In order to satisfy the requirements for the advanced systems used in modern wireless and radar applications, different multiband and reconfigurable antennas have been proposed and investigated in the past years. In this paper, these design concepts have been classified into three basic approaches: tunable/switchable antenna integration with radio-frequency switching devices, wideband or multiband antenna integration with tunable filters, and array architectures with the same aperture utilized for different operational modes. Examples of each design approach are discussed along with their inherent benefits and challenges.